2006
DOI: 10.1186/1748-717x-1-22
|View full text |Cite
|
Sign up to set email alerts
|

Radiation therapy planning with photons and protons for early and advanced breast cancer: an overview

Abstract: Postoperative radiation therapy substantially decreases local relapse and moderately reduces breast cancer mortality, but can be associated with increased late mortality due to cardiovascular morbidity and secondary malignancies. Sophistication of breast irradiation techniques, including conformal radiotherapy and intensity modulated radiation therapy, has been shown to markedly reduce cardiac and lung irradiation. The delivery of more conformal treatment can also be achieved with particle beam therapy using p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(18 citation statements)
references
References 64 publications
2
16
0
Order By: Relevance
“…[10][11][12][13], protons can be used in a manner that reduces normal tissue injury, owing to reduced scattering to normal tissues and the sharp dose fall-off at the end of the range. We documented the proton advantage in normaltissue sparing in several sites for which we compared proton and photon treatment plans, including IMRT photons; our observations echoed those reported by others [75][76][77][78]. The difference in the volume integral dose to normal tissues suggested to us that we could begin hypofractionating treatments in attempts to reduce overall treatment time and costs.…”
Section: Discussionsupporting
confidence: 82%
“…[10][11][12][13], protons can be used in a manner that reduces normal tissue injury, owing to reduced scattering to normal tissues and the sharp dose fall-off at the end of the range. We documented the proton advantage in normaltissue sparing in several sites for which we compared proton and photon treatment plans, including IMRT photons; our observations echoed those reported by others [75][76][77][78]. The difference in the volume integral dose to normal tissues suggested to us that we could begin hypofractionating treatments in attempts to reduce overall treatment time and costs.…”
Section: Discussionsupporting
confidence: 82%
“…Synchronous bilateral breast irradiation is challenging due to the large and complex target volume and the need to minimize the dose to the heart and lungs. IMRT, VMAT, and HT techniques have been reported to improve dosimetry in SBBC patients, and past dosimetric studies have shown that IMPT can reduce the cardiac dose significantly in unilateral breast cancer (11)(12)(13)(14)(15)(16)(17)(18)(19). Previous studies have not compared dosimetric differences between IMRT, VMAT, and HT in SBBC.…”
Section: Discussionmentioning
confidence: 99%
“…Past dosimetric studies have shown that proton therapy delivered a lower cardiac dose compared to photon techniques in unilateral breast cancer (16)(17)(18)(19). Intensity-modulated proton therapy (IMPT) has the advantage of improving the dose distribution and reducing the dose of organs at risk (OARs) more without being limited by complex anatomical structures.…”
Section: Introductionmentioning
confidence: 99%
“…Proton beam therapy results in greater sparing of healthy brain tissue and allows for a moretargeted delivery of radiation and smaller penetration of tissue beyond the tumor [94]. The mean dose of radiation to the hippocampus could be reduced much more, and it could be half that of IMRT and consequently reduce the risk of cognitive deficit after RT [95].…”
Section: Decline In Nonverbal Memory Was Observed In Patients Withmentioning
confidence: 99%